Democratic Parenting: Parental interpretation of parent education messages in the USA and Israel - Oryan, Shlomit (International Journal about Parents in Education, 2023)
The study examines the process of globalization of cultural knowledge as it occurs in the parent education system. The research explores, through comparative analysis and qualitative methods, how the same global knowledge regarding democratic parenting, produced by USA experts and imparted through parenting classes to parents in the USA and Israel, is interpreted and implemented by the parents. Although parenting theories are similar, parents in the two countries interpret and implement the theories differently, according to their cultural beliefs and socio-political background.